Comparison of coronary revascularization appropriateness for non‐acute coronary syndrome cases under the 2017 update vs the 2012 appropriate use criteria. Issue 4 (2nd October 2018) - Case, Brian C.; Geiser, Katherine M.; Torguson, Rebecca; Pichard, Augusto D.; Satler, Lowell F.; Waksman, Ron; Ben‐Dor, Itsik
Abstract: Objectives: To compare coronary revascularization appropriateness for non‐acute coronary syndrome cases under the 2017 update vs the 2012 appropriate use criteria (AUC). Background: In 2017, the 2012 AUC for coronary revascularization were updated. We examined how applying these new 2017 updates to our previous inappropriate cases would change their appropriateness. Methods: We identified 50 cases of patients who underwent coronary revascularization for stable ischemic heart disease who were deemed inappropriate under the 2012 AUC. Two separate physicians reviewed the cases and applied a new AUC based on the 2017 AUC. Next, if there was a change, the reason was identified. Results: Average age was 64, majority being male (29; 58%). Forty‐two (84%) were asymptomatic upon presentation. Most cases (27, 54%) dealt with percutaneous coronary intervention (PCI) of the right coronary artery. After applying the 2017 AUC, 34 of the 50 inappropriate failures (68%) would be changed from "inappropriate" to "may be appropriate care." Of the 34 cases, 25 (73.5%) were changed due to the new AUC no longer expecting the patient to be on ≥2 anti‐angina medications prior to PCI. Of the 34 cases, eight (23.5%) were changed due to the new AUC expanding the use of non‐invasive modalities. Conclusions: Applying the 2017 AUC led to a statistically higher number of cases being deemed "may be appropriate." The most common cause for the change included the change in requirement for anti‐angina regimen and the expanded role of non‐invasive modalities.